Trypanosoma (herpetosoma) Rangeli tejera, 1920: influence of host weight, size of inoculum, and route of infection upon experimental parasitemia - Tejero,Felix (1988)
To study the influence of host age, inoculum size, and route of infection on Trypanosoma (Herpetosoma) rangeli, 12 lots of 6.0 g albino mice (NMRI strain) were infected up. with from 25x10¹ to 25x10(6) trypomastigotes/gram body weight harvested from LIT medium. The lower inocula produced low but persistent parasitemias, while the higher inocula produced high levels of parasitemia that fell quickly, suggesting the mobilization of resistance mechanisms. In other experiments, i.p. inoculation produced higher parasitemias than s.c. inoculation, and 6.0 g mice had higher parasitemias than 16.0 or 26.0 g mice. Thus, a standard methodology would seem to be necessary in the study of the various strains and/or species that may make up the T. rangeli complex.